DIVERSITY OF THE CLOSED-NESTED HONEY BEES (APIDAE: APIS SPP.) AND THE TRADITIONAL HONEY COLLECTING AND BEEKEEPING IN FOUR ISLANDS OF INDONESIA - Sih Kahono; Djunijanti Peggie; Eko Sulistyadi (Treubia, 2021)
The closed-nested honey bees are an important group that has been successfully bred traditionally and in a modern way. The traditional honey beekeeping practices are still favorable by local people living near natural habitats. Many rural areas in Indonesia are well known as producers of honey from the traditional honey collecting and traditional honey beekeeping of the closed-nested honey bees. However, there is limited information on the diversity of the honey bees that had supported the honey productions and their traditional honey beekeeping. This research was to provide an overview of the diversity of the honey bee species that are used in the wild honey collecting and their traditional honey beekeeping in four selected study sites in the islands of Java, Bawean, Kalimantan, and Peleng. We recorded three species of closed-nested native honey bees in the traditional honey collecting and traditional honey beekeeping, namely Apis cerana, A. koschevnikovi, and A. nigrocincta. We observed that traditional beekeeping of A. cerana was carried out in Tasikmalaya and Bawean Island, and that of A. cerana and A. koschevnikovi were carried out in Kayan Hilir. On Peleng Island, people do not do beekeeping but collect honey directly from the forest. Honey collecting and beekeeping practices are related to changes in the seasons of the flowering period in their habitats. The knowledge of the flowering period is needed to know the seasonal movement of honey bees from forest to village and vice versa.